Comparison of accelerometer‐measured sedentary behavior, and light‐ and moderate‐to‐vigorous‐intensity physical activity in white‐ and blue‐collar workers in a Japanese manufacturing plant. Issue 3 (25th May 2018) - Fukushima, Noritoshi; Kitabayashi, Makiko; Kikuchi, Hiroyuki; Sasai, Hiroyuki; Oka, Koichiro; Nakata, Yoshio; Tanaka, Shigeho; Inoue, Shigeru
Abstract : Objective: The times spent in sedentary behavior (SB) and moderate‐to‐vigorous physical activity (MVPA) are independently associated with health outcomes; however, objective data on physical activity levels including SB among different occupations is limited. We compared accelerometer‐measured times spent in SB, light‐intensity physical activity (LPA), and MVPA, and the patterns associated with prolonged bouts of SB between white‐ and blue‐collar workers. Methods: The study population consisted of 102 full‐time plant workers (54 white‐collar and 48 blue‐collar) who wore a triaxial accelerometer during waking hours for 5 working days. Accelerometer‐measured activity levels were categorized as SB (≤ 1.5 metabolic equivalents (METs)), LPA (1.6‐2.9 METs), and MVPA (≥ 3.0 METs). A sedentary bout was defined as consecutive minutes during which the accelerometer registered less than ≤ 1.5 METs. Accelerometer variables were compared between white and blue‐collar workers through analysis of covariance. Results: During working hours, white‐collar workers spent significantly more time in SB and less time in LPA than blue‐collar workers (SB: 6.4 h vs. 4.8 h, 73% vs. 55% of total work time; LPA: 1.9 h vs. 3.5 h, 22% vs. 40% of total work time, p <.001), whereas the MVPA time was similar between the groups. White‐collar workers spent significantly more SB time in prolonged sedentary bouts (≥30 min) compared to blue‐collar workers. During leisure time, the SB, LPA, and MVPA times were similar between the groups. Conclusions: White‐collar workers have significantly longer SB times than blue‐collar workers during work hours, and do not compensate for their excess SB during work by reducing SB during leisure time.